2013
DOI: 10.1111/echo.12498
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue Thickness in Hemodialysis Patients

Abstract: Epicardial adipose tissue thickness may be a useful indicator of early atherosclerosis in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Bettencourt et al [ 41 ] showed that EFT is directly related to gender, age, BMI, waist circumference, abdominal visceral fat tissue, and atherosclerotic load. EFT is associated with BMI in females with DM [ 11 ] and was higher in females with a BMI >27 kg m -2 [ 16 ]. Moreover, EFT is an independent predictor of intra-abdominal visceral fat tissue [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bettencourt et al [ 41 ] showed that EFT is directly related to gender, age, BMI, waist circumference, abdominal visceral fat tissue, and atherosclerotic load. EFT is associated with BMI in females with DM [ 11 ] and was higher in females with a BMI >27 kg m -2 [ 16 ]. Moreover, EFT is an independent predictor of intra-abdominal visceral fat tissue [ 42 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial fat thickness (EFT) is associated with the thickness of visceral fat tissue [ 9 ]. In addition to being an anatomical barrier, epicardial fat tissue is also a local reserve for proinflammatory cytokines [ 10 ] and is related to obesity, hypertension, insulin resistance and coronary artery disease [ 11 16 ]. Currently, EFT measurement is performed via transthoracic echocardiography (TTE), magnetic resonance imaging (MRI) and multi-slice computed tomography (CT) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While EATT is positively correlated with CIMT in several diseases (Iacobellis and Willens 2009 ; Altun et al 2014 ; Natale et al 2009 ; Kim et al 2013 ), to our knowledge no data are available on the potential role of EATT in predicting early atherosclerosis as well as CIMT in patients with ADPKD. Therefore, our study was designed to evaluate the relationship between echocardiographic EATT and CIMT, as predictors of early atherosclerosis, in normotensive ADPKD patients.…”
Section: Introductionmentioning
confidence: 96%
“…CIMT is a well-known independent predictor of cardiovascular diseases and recognized as a novel marker of subclinical atherosclerosis (Polak et al 2011 ). In addition, on the basis of its strong correlation with obesity, insulin resistance, metabolic syndrome, hypertension, diabetes, and subclinical atherosclerosis (Polak et al 2011 ; Iacobellis and Willens 2009 ); echocardiographic measurement of epicardial adipose tissue thickness (EATT) has also been indicated to be a potential marker of atherosclerosis and of CIMT and thus might be used as a simple tool for predicting cardiometabolic risk (Polak et al 2011 ; Iacobellis and Willens 2009 ; Altun et al 2014 ; Chaowalit et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Again, a study including 62 hemodialysis patients identified a strong relationship between CIMT and EFT thickness. 35 Nakanishi et al 36 used computed tomography to measure EFT levels and reported that patients with high levels had more coronary artery calcification. In studies by Cece et al 12 and Resorlu et al, 37 CIMT values in AS patients were found to be higher than those of the control group.…”
Section: Discussionmentioning
confidence: 99%